2020
DOI: 10.5999/aps.2019.01571
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet-rich plasma and modified nanofat grafting in infected ulcers: Technical refinements to improve regenerative and antimicrobial potential

Abstract: Background Surgical reconstruction of chronic wounds is often infeasible due to infection, comorbidities, or poor viability of local tissues. The aim of this study was to describe the authors’ technique for improving the regenerative and antimicrobial potential of a combination of modified nanofat and platelet-rich plasma (PRP) in nonhealing infected wounds.Methods Fourteen patients met the inclusion criteria. Fat tissue was harvested from the lower abdomen following infiltration of a solution of 1,000 mL of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Among patients who were referred to specialties, those with a low SEP had poor accessibility to frequent clinical visits because of cost or location. DFUs account for a large proportion of rising health care costs for persons with diabetes [35,36]. This would The strength of this study is that its target sample group was randomly selected which can represent the total South Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who were referred to specialties, those with a low SEP had poor accessibility to frequent clinical visits because of cost or location. DFUs account for a large proportion of rising health care costs for persons with diabetes [35,36]. This would The strength of this study is that its target sample group was randomly selected which can represent the total South Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies concerning to combination of PRP application and fat grafts were found, and three of those were RCTs [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Eight articles fell under the category "reconstruction," focusing on chronic ulcers and wounds (three), scars (three), or breast reconstruction (two).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two authors reported the use of CaCl and/or Thrb for platelet activation [11, 13-15, 18, 19, 21, 24, 28, 30, 31, 37, 39, 42-47, 50, 51, 58]. Nonactivated PRP (na-PRP) was applied in 6 cases [34,[52][53][54][55]57], and two authors reported the use of both na-PRP and a-PRP [22,23]. One author applied photo-activated PRP [40].…”
Section: Prp Preparationmentioning
confidence: 99%
“…Segreto et al [ 94 ] evaluated the role of a combination of nanofat grafting with autologous PRP in non-healing infected wounds. The application of nanofat with the micro-needling technique improved the delivery of cellular components into fibro-sclerotic tissues and enhanced the regeneration of soft tissue in chronic non-healing wounds.…”
Section: Applications Of Nanofatmentioning
confidence: 99%